Identifying the effect of product types in the relationships between product discounts and consumer distrust levels in China’s online social commerce market at the era of big data - Li, Lin; Rhee, Cheul; Moon, Junghoon (KSII Transactions on Internet and Information Systems, 2018)
In the era of big data, consumers capture more and more economic surplus yet the seed of distrust also grows with the fast-spreading of social commerce, this paper began with the idea that product types may determine the degree of consumers’ distrust even when identical discounts are offered for those products on Chinese social commerce websites. We also attempted to determine if distrust negatively affected consumers’ purchase attitudes. 20 representative products that are commonly sold on social commerce websites in China were chosen to examine the relationships among product types, discount rates, distrust levels, and purchase attitudes. Inductive interview was used to collect the data as well as consumers’ perceptions of the relationships. Data analysis results suggested that consumers like deep discounts, but their distrust levels increase along with the discount rates, however, the levels of increasing distrust vary according to product types. High, medium, and low discount rate categorizations were made and three propositions were suggested. This paper will contribute to the body of knowledge on online social commerce market and provide valuable implications for e-retailers and general consumers in online social commerce websites in China.
Keywords: Body of knowledge; Consumer distrust; Discount rates; Economic surplus; Product discounts; Product types; Social commerces; Consumer distrust; Product discounts; Product types; Purchase attitudes; Social commerce